On the Difference Equation xn=anxn-k/(bn+cnxn-1⋯xn-k) - Stevo Stević; Josef Diblík; Bratislav Iričanin; Zdeněk Šmarda (Abstract and Applied Analysis)
The behavior of well-defined solutions of the difference equation xn=anxn-k/(bn+cnxn-1⋯xn-k), n∈ℕ0, where k∈ℕ is fixed, the sequences an, bn and cn are real, (bn,cn)≠(0,0), n∈ℕ0, and the initial values x-k,…,x-1 are real numbers, is described.